The Relation Between Cardiovascular Load With Dehydration And Fatigue In Forging Iron Workers In The Village Center Industrial Iron Pande Padas Karanganom District Klaten - Angling Margiasih, Ocky A (2016)
Severity of work is strongly influenced by the type of physical activity and the work environment. The pulse is one of the body's physiological variables that can be used to determine the severity of the workload. The work environment can affect the body's system that could lead to an increase in pulse rate, spend a lot of perspiration, loss of balance and fatigue. This research aims to determine the relationship between the burden of cardiovascular dehydration and knowing the relationship between the burden of cardiovascular fatigue. This research was an observational study with cross sectional design with using total sampling methods as the sampling technique. Based on %cvl measurement as much as 75% were in the middle category and as much as 25% were in the heavy category. The measurement reserach of dehydration as much as 3,1% in the category of mild dehydration, 84,4% medium category, and 12,5% category of severe dehydration and exhaustion obtained for as much as 15,6% had mild fatigue, tired of being 50%, 31,3% tired weight, and 3,1% heavy tired. Bivariate analisys used the Pearson Product Moment, with significance 0.05, got result (P = 0.016) or (P <0.05) which meaned had the relations between %CVL with dehydration in a low score r = 0,423 wich meaned the relations between 2 variables weremoderate and the obtained reserach (p = 0,018) or (p < 0,05), which meaned had the releations between %CVL with fatigue in a low score r = 0,415 wich meaned the relations between 2 variables were moderate. Key Words: %CVL, Dehydration, Fatigue